Local Wisdom in Shifting Cultivation Management of Dayak Ngaju Community, Central Kalimantan - Eti Dewi Nopembereni; Sugiyanto Sugiyanto; Keppi Sukesi; Yayuk Yuliati (Publisher of Widyagama University of Malang (UWG Press), 2019)
This study aims to identify the local wisdom in the management system of shifting cultivation in Dayak Ngaju, Central Kalimantan. The study was conducted at Mantangai Tengah Village and Mantangai Hilir Village, Mantangai District, Kapuas Regency, Central Kalimantan. Purposive sampling was used as the method to determine the location and sample of the research (70 people). The primary data used were farmers or cultivators and key informants while the secondary data were obtained from BPS and related agencies. The analysis of the data was done by using a descriptive qualitative technique. The results show that the management system of shifting cultivation conducted by local people cannot be separated from the local wisdom in the community. This is indicated by some activities which explain that phenomena such as forest clearing, land burning, land management, technology utilization, and ceremony accompanying the activities of shifting cultivation. Communities live in a harmonious relationship with forests and land, manage land in a limited area (1-2 ha) without the risk of land fires, live in communal and mutual cooperation (gotong-royong), and have local knowledge that has a positive value.JEL Classification: D19, O33, O35